Review Paper on Wireless Sensor Networks using Different Types of Approaches - Imam, Diba; Shrivastava, Rajdeep (International Journal of Computer Sciences and Engineering, 2019)
The widespread use of wireless sensor devices and their advancements in terms of size, deployment cost, measurement of environmental events and user friendly interface have given rise to many applications of wireless sensor networks (WSNs). WSNs are usually characterized as self-organizing networks which can be deployed without requiring any specific infrastructure in harsh and/or hostile area. In this paper are studied of different types of clustering protocol favors higher period in lieu of overall network lifetime. In cluster, a predetermined number of CHs are selected in deterministic fashion on the basis of residual energy of nodes. The focus is to balance the load among nodes and provide full network coverage.